MicroRNA in regenerative medicine - Sen, Chandan K. (Academic Press, 2015)
This work encapsulates the uses of miRNA across stem cells, developmental biology, tissue injury and tissue regeneration. In particular contributors provide focused coverage of methodologies, intervention and tissue engineering. Regulating virtually all biological processes, the genome's 1048 encoded microRNAs appear to hold considerable promise for the potential repair and regeneration of tissues and organs in future therapies. In this work, 50 experts address key topics of this fast-emerging field. Concisely summarizing and evaluating key findings emerging from fundamental research into t.